Nexus between Corporate Social Responsibility Practices and Sustainable Livelihood in Nigerian Oil and Gas Production Region - Mbateman Chondough , Stephanie (Competitio, 2021)
Oil and Gas remains the backbone of the Nigerian economy as it constitutes a major revenue source for the government. However, host communities have not felt the effect of carrying the financial burden of the nation. The heavy reliance on the oil sector has crippled instead of enhanced the environmental and social conditions of the host communities. This study examines the nexus between CSR practices and sustainable livelihood in the Nigerian oil and gas production region using secondary data. The study concludes that oil firms have underperformed within the scope of the usage of CSR to mitigate environmental and social concerns. Attention should be drawn to the peaceful coexistence of the oil firms and the community members in the affected region. CSR initiatives, together with government interventions, will greatly improve the livelihoods of the people. It is recommended that oil firms recognize their obligations to all stakeholders, the environment and the expectations of the host communities and establish a relationship that will foster a working partnership for community development and peaceful coexistence.JEL Code: M14, Q35, Q56